2020
DOI: 10.3847/1538-4365/ab5c26
|View full text |Cite|
|
Sign up to set email alerts
|

Compact Groups of Galaxies in Sloan Digital Sky Survey and LAMOST Spectral Survey. I. The Catalogs

Abstract: Compact group (CG) is a kind of special galaxy system where the galaxy members are separated at the distances of the order of galaxy size. The strong interaction between the galaxy members makes CGs ideal labs for studying the environmental effects on galaxy evolution. Traditional photometric selection algorithm biases against the CG candidates at low redshifts, while spectroscopic identification technique is affected by the spectroscopic incompleteness of sample galaxies and typically biases against the high … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 104 publications
0
9
0
Order By: Relevance
“…The WAVES-WIDE(-DEEP) surveys aiming to cover an area of ∼70 (1200) deg 2 , identifying ∼50,000 (20,000) dark matter halos down to a mass of 10 14 (10 11 ) M and out to a redshift of z phot 0.2 (0.8). As with X-ray selected objects, optically selected groups are physically heterogenous systems (e.g., see the dynamical analysis by Zheng and Shen [239] for a sample of compact groups). However, it is possible that the physical processes at work in the IGrM of optically-and X-ray-selected systems are different.…”
Section: Galaxy Groups With the Next-generation Instrumentsmentioning
confidence: 99%
“…The WAVES-WIDE(-DEEP) surveys aiming to cover an area of ∼70 (1200) deg 2 , identifying ∼50,000 (20,000) dark matter halos down to a mass of 10 14 (10 11 ) M and out to a redshift of z phot 0.2 (0.8). As with X-ray selected objects, optically selected groups are physically heterogenous systems (e.g., see the dynamical analysis by Zheng and Shen [239] for a sample of compact groups). However, it is possible that the physical processes at work in the IGrM of optically-and X-ray-selected systems are different.…”
Section: Galaxy Groups With the Next-generation Instrumentsmentioning
confidence: 99%
“…However, when radial velocities became available, concordant triplets were allowed in the sample (Hickson et al 1992). Also, McConnachie et al (2009) and Zheng & Shen (2020) have introduced CG catalogues including triplets. Following these works and allowing to have triplets among the CGs, we adopted a minimum number of three galaxies and a maximum of ten.…”
Section: Compact Groupsmentioning
confidence: 99%
“…To perform statistical studies of these peculiar systems, until today astronomers apply similar criteria to different observational samples of galaxies but using automatic algorithms (Prandoni et al 1994;Iovino 2002; Iovino et al 2003;Lee et al 2004;de Carvalho et al 2005;McConnachie et al 2009;Díaz-Giménez et al 2012;Sohn et al 2015;Díaz-Giménez et al 2018;Zheng & Shen 2020). Other authors identified compact groups using percolation algorithms (for example the friends-of-friends algorithm) but trying to mimic the main characteristics of the Hickson CGs ( Barton et al 1996;Allam & Tucker 2000;Focardi & Kelm 2002;Hernández-Fernández & Mendes de Oliveira 2015;Sohn et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They found that only 44% of the SHONCGs are also in HMCG sample. Recently, Zheng & Shen (2020) identified a large sample of CGs with redshifts information also in SDSS-DR12 survey, using a relaxed Hickson-like criteria. The percentage of groups in common with previous samples is very poor and suggests that the population of CGs identified by different authors is different.…”
Section: Introductionmentioning
confidence: 99%